Influence of morphology on the blinking mechanisms and the excitonic fine structure of single colloidal nanoplatelets. Issue 48 (29th November 2018) - Hu, Zhongjian; Singh, Ajay; Goupalov, Serguei V.; Hollingsworth, Jennifer A.; Htoon, Han
Abstract : Photoluminescence spectroscopy of single CdSe/CdZnS nanoplatelets reveals that shell morphology strongly affects the blinking mechanisms and the fine electronic structure splitting. Abstract : Colloidal semiconductor nanoplatelets with a similar electronic structure as quantum wells have recently emerged as exciting materials for optoelectronic applications. Here we investigate how morphology affects important photoluminescence properties of single CdSe and core/shell CdSe/CdZnS nanoplatelets. By analyzing photoluminescence intensity-lifetime correlation and second-order photon correlation results, we demonstrate that, irrespective of the morphology, Auger recombination plays only a minor role in dictating the blinking behavior of the nanoplatelets. We find that a rough shell induces additional nonradiative channels presumably related to defects or traps of an imperfect shell. Furthermore, polarization-resolved spectroscopy analysis reveals exciton fine-structure splitting of the order of several tens of meV in rough-shell nanoplatelets at room temperature, which is attributed to exciton localization and is substantiated by theoretical calculations taking into account the nanoplatelet shape and electron–hole exchange interaction.